Smirnov I.V. Wear resistant increase of metal-ceramic coatings on the basis of clad powders. - Смирнов, И.В. (Problems of Tribology, 2014)
Reserves for application of coatings on the basis of traditional metals and alloys are limited, especially at the decision of problems of related to wear resistant. Metal-ceramic coatings on the basis of oxide and carbide powders are most effective for recovery, lifetime increase as well as reliability of details serving under the conditions of abrasive wear.The use of these powders at thermal spraying and facing has the certain difficulties related to the processes of decomposition of carbides at high temperatures and low adhesion and cohesion of the oxide coatings due to the thermal expansion coefficient difference. The elimination of the negative effects achieved by decreasing (localizations) of thermal influence at spraying of the coating and also deposition cladding shell on the powder particles. A vacuum-arc method allowing forming nanostructure coatings from any metals and alloys with high adhesion to ceramic was used for cladding of the powder.Wear-resistant coatings on the basis of technologies of the electron-beam deposition and plasma spraying with the use of the ceramic powders with cladding metallic shells created by the vacuuming-arc method are developed. The wear resistant of the coating rose in 1.5–2.5 times at the electron-beam deposition, as a result of decrease of dissolution of tungsten carbide particles with copper shells. The use of alumina powder with clad shells from titan and aluminium at plasma spraying provided the increase of microhardness, cohesion strength and wear resistant of coating attended with the increase of rider wear in 2–2.2 times.